No need to justify your choice: pre-compiling line breaks to improve eBook readability - Pinkney, Alexander J.; Bagley, Steven R.; Brailsford, David F. (2013)
Implementations of eBooks have existed in one form or another for at least the past 20 years, but it is only in the past 5 years that dedicated eBook hardware has become a mass-market item.